Analisis Gelombang Air Laut dengan Menggunakan Pemodelan Berbasis Matlab - Zainur Rasyid Ridlo; Luthfin Afafa; Efrika Marsya Ulfa; Mawardani Adi Pratama Dewi; Siti Maimuna (jcgant, 2021)
Waves are the propagation of energy from one place to another without dragging the material in its path. The waves on Papuma Beach are classified as technical waves because they require a medium to propagate and transfer the required energy. When the waves move at a certain height, the waves on Papuma Beach have a potential force. This potential force depends on the height of an object. When the waves on Papuma Beach get higher, it also has high potential energy. The method used in this research is the analysis of physical concepts related to the indigenous. Research method of analyzing the concept of physics, analyze the formulas and quantities used coding the MATLAB for making illustrations and to calculate the formulas. Potential energy is formulated with. The energy in the waves is a combination of kinetic energy and potential energyand thanproduce the formula.